LGR5 marks targetable tumor-initiating cells in mouse liver cancer - Wanlu Cao (Nature Portfolio, 2020)
Cancer stem cells (CSCs) are thought to be the main drivers for disease progression and treatment resistance in liver cancer. This study identifies the LGR5+ compartment as an important CSC population, representing a viable therapeutic target for combating liver cancer.